PHYSICAL THERAPY ATHLETES OF GAME SPORTS AFTER ARTHROSCOPIC TREATMENT OF KNEE JOINT INJURIES (Physical Culture and Sport: Scientific Perspective, 2024)
Knee injuries are one of the most common problems among athletes in game sports such as football, basketball, handball and volleyball. Given the high loads on the musculoskeletal system during rapid movements, jumps and sudden changes in the direction of movement, athletes of these sports often suffer damage to the structures of the knee, including the menisci, ligaments and cartilage. The purpose of the study: to develop a program to improve the functional state of the knee joint in athletes of game sports after arthroscopic treatment and experimentally evaluate its effectiveness. Research methods. Theoretical research methods were used in the work: analysis, comparison, induction, deduction, systematization and generalization of scientific and methodical literature, pedagogical experiment, medical and biological methods, methods of mathematical statistics. Work results. At the end of the study, the index of knee joint flexion in athletes of the main group was significantly higher compared to the control group by 25.74 degrees (p0.05). In the main group, there was a significant improvement in the strength of the knee joint flexors by 1.82 points (p
Keywords: injuries; physical therapy; balance training; football players